University examination timetabling algorithm based on genetic algorithm - Capacillo, Annie C. (2004)
Examination timetabling deals with the scheduling of exams to the set of time slots subject to some constraints. Genetic algorithm was used as framework in making the examination timetabling algorithm. An algorithm for each genetic algorithm operators such as initialization, evaluation, selection, recombination, repair and mutation was developed to apply in the examination timetabling problem. The examination timetabling algorithm developed start with obtaining the initial population then evaluating each timetable and the population. After which, the parent timetables are selected and then recombined to produce a new set of populations. The recombined timetable is repaired to maintain feasibility and mutated afterwards. Whichever of the repaired and mutated population has the higher evaluation is compared to the previous population. If the produced population has the higher evaluation than the previous population, it will undergo the same process again, else the iteration stops and the previous population will be the set of the final timetables. The algorithm also end if the number of iteration predetermined is reached. Using the data of the University of the Philippines in Mindanao, the evaluation of the population after three iterations is higher by 0.093015262 compared with the initial population. Since this was done manually, it is recommended to encode the algorithm into a computer program. This study presented only one process of the possible combination of initialization, evaluation, selection, recombination, repair and mutation. It is thus recommended to experiment on the combination of these genetic algorithm operators in order to understand better and improve the performance of the genetic algorithm applied to the timetabling problem.
Thesis (BS Applied Mathematics) -- University of the Philippines Mindanao, 2004